Quality of life assessment in Egyptian rheumatoid arthritis patients: Relation to clinical features and disease activity - Gamal, Rania M.; Mahran, Safaa A.; Abo El Fetoh, Noha; Janbi, Fadwa (Egyptian rheumatologist, 2016)
To assess the impact of rheumatoid arthritis (RA) on the health related quality of life (QoL) of patients, using the 36-item short form (SF-36) and to study the influence of different disease variables. Eighty-six RA patients were recruited from the Rheumatology and Rehabilitation outpatient of Assiut University Hospital. Forty-three, age and sex matched subjects were included as controls. The QoL was measured in all subjects using the SF-36 health survey. Disease activity was assessed in RA patients by the disease activity score (DAS28). All domains of the SF36 were significantly lower in the patients (p<0.0001). Patients with a lower educational level and those unemployed had significantly lower SF36 components. Those with a disease duration >5years, positive rheumatoid factor and higher disease activity had a significantly lower SF36 physical component. Patients receiving hydroxychloroquine or prednisolone had significantly lower mental component. Significant negative correlation of the SF36 physical and mental components was found with both disease duration (p=0.01 and p<00001 respectively) and DAS28 (p<0.0001 for both). Rheumatoid factor negatively correlated with the physical component (p<0.0001). Regression analysis showed that disease duration was the most profound predictor of both SF36 components (p<0.0001). The quality of life is impaired in Egyptian RA patients and disease duration was the most significant predictor. Routine assessment of the health-related QoL in those patients is recommended to detect and monitor the impact of the disease and medications used on different aspects of their quality of life.